The effect of open green space on the stress level of Bogor Botanical Garden visitors - Yuriko Asahiro; Arzyana Sunkar; Jarwadi Budi Hernowo (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Stress is a global phenomenon that has become a part of everyday life. Stress can be triggered by the presence of stressors. In Indonesia, the prevalence of psychological stress keeps increasing. This study aims to analyze the perceived restoration effect of green open parks on the stress levels of Bogor Botanical Gardens visitors. A survey of 100 visitors of Bogor Botanical Garden was conducted based on the Perceived Stress Scale. Data on respondent characteristics and stress levels were analyzed using descriptive analysis, the visitor's characteristics that affected their stress levels were analyzed using stepwise linear regression and analysis of variance, and the effect of having a garden and the proximity to open green space on the visitor's stress levels were identified using analysis of variance. The respondents who felt low, medium, and high-stress levels, were 22%, 73%, and 5% respectively. The majority of the respondents perceived Bogor Botanical Garden as restorative. Factors that significantly affect the stress level of respondents are age and purpose of visit. The older the respondent, the lower their stress level tends to be. Visitors who visit for exercise/health activities have significantly lower stress levels than for other visits. In this study, no significant relationship was found between garden ownership and proximity to green parks on the stress level of the respondents.